Determinants of ICT usage among low-income groups in Colombia, Mexico, and Peru (2010)
The authors examine the determinants of information and communications technology (ICT) usage among low-income people in three developing countries: Colombia, Mexico, and Peru. Using two composite indicators, they focus on cross-country differences and similarities in ICT usage across gender, age, education, and income levels. The authors' analysis indicates that the single most important factor limiting the digitalization of low-income people in all three countries was lack of education. The impact of income itself was low although positive. Their findings also suggest that comprehensive measures that mix standard ICTs with very advanced ones can be misleading. © Taylor and Francis Group, LLC.